ИГРОВЫЕ ТЕХНОЛОГИИ В ОБУЧЕНИИ ИНОСТРАННЫМ ЯЗЫКАМ: ТЕОРЕТИЧЕСКИЕ ОСНОВАНИЯ И ПЕДАГОГИЧЕСКИЙ ПОТЕНЦИАЛ - Нуратдинова, Н.Б. (SCIENCE and SOCIETY, 2025)
This article explores the role of game-based technologies in foreign language teaching, emphasizing their theoretical foundations and pedagogical potential. It highlights the distinctive value of pedagogical games in enhancing motivation, communicative competence, and learner engagement. Particular attention is given to the teaching of English prepositions, where games provide contextualized practice and support sustained interest. The study underscores the need to further develop game-based approaches in line with current educational reforms in Uzbekistan.
Keywords: game-based learning; pedagogical games; English prepositions; communicative competence; motivation; primary education